GEDUNG PEMBINAAN OLAHRAGA BULU TANGKIS TUNTUNG PANDANG TANAH LAUT - Dini, Nur Elma; Wastuty, Prima Widia (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Badminton Tuntung Pandang Tanah Laut Sports Development Building is a place designed to meet the needs of an athlete to channel the talents and abilities possessed by individuals and groups. The high interest of the community in badminton is not comparable with the achievements that should be able to be achieved. The aim to advance the achievements of badminton in Tanah Laut can be achieved with good coaching, the available facilities are able to support the needs of athletes, as well as attractive building designs that will affect the attractiveness of the community in badminton sports thereby opening up greater opportunities for get young players in delivering regional athletes who excel. Iconic architectural approach to buildings, through the character of badminton whose elements in addition to supporting the function of building sports buildings as well as meeting the criteria of the iconic architectural concept, which has a magnificent building scale, has an attractive shape that is easily recognizable, functional and geometric, and has robustness through structural expression. So that the exterior of the building is able to convey the message of the building as a building for Badminton Tuntung Pandang Tanah Laut through the forms and design of the facade with badminton characteristics themselves. Then the building design is expected to be able to provide good facilities, attractive buildings, and be able to give birth to athletes who excel.